Relationship Between Knowledge Level and Community Behavior about Eradication of Mosquito Nest - Putu Intan Daryaswanti; G.A.A. Sintha Fransisca Devi; Ni Made Diah Pusparini Pendet; Komang Agus Jerry Widyanata (Babali Nursing Research, 2021)
Introduction: Dengue hemorrhagic fever is one of the population's health issues in Indonesia, with an increasing number of sufferers as the disease spreads. The cases rose dramatically in Panji Village, with a significant spike in cases per year. In 2018 there were 16 cases, in 2019 it increased to 177 cases and in 2020 until February 122 cases were recorded. Mosquito nest eradication is the most reliable, safe, and cost-effective method of eliminating dengue fever vectors. The aim of this study is to know relationship the level of knowledge and behavior regarding mosquito nest eradication in Panji Village. Methods: The design used was descriptive correlation with a cross sectional approach. The population of this study is the population living in the Banjar area, Dinas Dangin Pura Panji Village Sukasada, Bali with 1222 residents, after entering the Slovin’s formula, 400 samples were obtained using purposive sampling technique. The instrument used to collect data in this study was a questionnaire sent via google form. Test the relationship using the Pearson test. Results: Most people have less knowledge and behavior and when viewed from the correlation test, a significant value of p = 0.000 is obtained with a value of r = 0.524 which means that the relationship is moderate and has a positive value. Conclusion: There is a moderate and positive relationship between knowledge and behavior in the Eradication of Mosquito Nests.